PENGARUH KONSENTRASI GULA TERHADAP ORGANOLEPTIK DAN SIFAT KIMIA ANGGUR BUAH TOMI-TOMI (Flacourtia inermis Roxb) - Rachel Breemer; Erynola Moniharapon; James Nimreskosu (Universitas Pattimura, 2016)
This research was aimed to determine the exact sugar concentration on the organoleptic and chemical properties of tomi-tomi fruit wine. A completely randomized experimental design with three levels sugar concentration 30, 40, and 50% were repeat three times therefore there were a total of nine experimental units. Result showed that 50% sugar concentration had the best organoleptic characteristic that was able to produce wine having 1,27% ethyl alcohol, 21,23% sugar content and a pH of 3,6.